Implementation of Teacher Competency Standards at Integrated Islamic Elementary Schools - Khoirotul Izzah (Center for Studies in Advanced Science, 2025)
Islamic education plays a vital role in shaping students' character and moral values in accordance with Islamic teachings. In this context, teachers serve as key actors in the educational process, requiring competency standards aligned with Islamic educational principles. This study aims to analyze the implementation of teacher competency standards at SDIT Mutiara Cendikia Lubuklinggau, an Islamic elementary school that integrates Islamic values into its learning practices. Using a qualitative approach and a case study method, data were collected through interviews, observations, and document analysis. The results reveal that teachers at SDIT Mutiara Cendikia implement competency standards encompassing strong Islamic understanding, morality and ethics, character education, pedagogical skills, involvement in the Muslim community, professional development, openness to diversity, academic qualifications, and concern for students’ safety and health. These findings demonstrate that the integration of Islamic values into teacher competency standards effectively strengthens the holistic educational role of teachers. The implications of this study provide valuable insights for the development of teacher competency models in other Islamic schools and serve as a reference for policymakers in enhancing the quality of Islamic education.